OPTIMIZATION OF TENOXICAM LOADED NIOSOMES USING QUADRATIC DESIGN - Shaji, Jessy; Shah, Akshay (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objective of the present study was to obtain an optimized formula of Tenoxicam (TNX) niosomes using Quadratic Design. Methods: TNX niosomes were prepared by Organic Solvent Injection method and all vehicles were evaluated for their entrapment efficiency (EE%), and Particle Size(nm). Results: EE% was found to be between 77.88 and 89.98. Percentage entrapment efficiency was significantly affected by the applied processing variables such as the concentration of span 60 as well as cholesterol. The mean vesicle size of drug loaded niosomes of the different batches ranged between 79-190 nm. Vesicle size of drug loaded niosomal batches was found to decrease as the concentration of span increases. The effects of all the tested independent variables have P-values<0.05. Conclusion: Quadratic design succeeded in the optimization of the formulation ingredients on EE% and particle size of Tenoxicam niosomes. Finally the optimization process provides a formula having the optimum level of factors.